Abnormal bone mineral content and density in people with tetrasomy 18p. Issue 3 (13th January 2019) - Moreira, Alvaro; Das, Hrishikesh; Hasi‐Zogaj, Minire; Soileau, Bridgette; Hill, Annice; Bruder, Jan M.; Hale, Daniel E.; Cody, Jannine D.
Abstract : Tetrasomy 18p is a rare chromosomal abnormality, resulting from an additional iso‐chromosome composed of two copies of the short arm. It is characterized by craniofacial abnormalities, neuromuscular dysfunction, and developmental delay. The Chromosome 18 Clinical Research Center has established the largest cohort of individuals with this rare genetic condition. Here, we describe a case series of 21 individuals with tetrasomy 18p who have a previously unreported clinical finding: low bone mineral density. Most individuals met criteria for low bone density despite being relatively young (mean age of 21 years). Clinicians providing care to individuals affected by Tetrasomy 18p should be aware of their increased risk for decreased bone density and pathological fractures.